A new deformation assisted tube-to-tubesheet joining process. (June 2021) - Alves, L.M.; Afonso, R.M.; Martins, P.A.F.
Abstract: This paper presents a new deformation assisted process for attaching tubes to tubesheets. The process is named 'joining by flaring and indentation' and consists in forming a single-lap flange by compressing the free tube end with a contoured die and indenting the tubesheet by pressing the tube flange against its surface. The process is carried out in a single stroke at ambient temperature and requires no surface preparation nor preliminary machining of grooves in the tubesheet holes. The presentation draws from the working principle and deformation mechanics of the new process to the identification of the operating parameters, typical deformation modes and required forming forces. Destructive pull-out tests are performed to determine the maximum force that the new joints are capable to withstand without failure by detachment. Numerical simulation with a finite element computer program gives support to the presentation. Highlights: Innovative deformation assisted joining process for attaching tubes to tubesheets. Numerical and experimental work to demonstrate its applicability. Easy replacement of tubes by avoidance of seal welds and grooves in the tubesheets. Destructive pull-out tests to evaluate the force to detach the tubes from the tubesheets.